Over Singapore - Koh, Tommy; Koh, Richard W. J. (Singapore : Editions Didier Millet, 2015)
Singapore: small tropical island and dynamic city, where some of Asia's Tallest buildings tower over modest quayside shophouses. Few landscapes, coastlines have been transformed as rapidly as those of Singapore. Seen from the air, the island revealed as a spectacular landscape of intricate patterns, rich textures and diverse colors. Stunning images show the true and unexpected variety of this city-state, providing a fresh perspective from which to view its landmarks and to explore the less-well-known sights of its industry, agriculture and outlying islands. In Over Singapore, award-winning Singaporean photographer Richard W. J. Koh showcases the dynamism of this ever-changing nation. His photographs are complemented by the insightful fext and captions of diplomat and international lawyer Professor Tommy Koh who provides a revealing historical introduction to the book and an insider's guide to the north, south, east and west of the country.
Includes index.
Keywords: Singapore -- History; Singapore--Pictorial works